Islet Transplantation Reverses Podocyte Injury in Diabetic Nephropathy or Induced by High Glucose via Inhibiting RhoA/ROCK/NF-κB Signaling Pathway. (10th March 2021) - Huang, Chongchu; Zhou, Yi; Huang, Hongjian; Zheng, Yushu; Kong, Lijun; Zhang, Hewei; Zhang, Yan; Wang, Hongwei; Yang, Mei; Xu, Xiaona; Chen, Bicheng
Abstract : Objective . Abnormal signaling pathways play a crucial role in the mechanisms of podocyte injury in diabetic nephropathy. They also affect the recovery of podocytes after islet transplantation (IT). However, the specific signaling abnormalities that affect the therapeutic effect of IT on podocytes remains unclear. The purpose of this study was to assess whether the RhoA/ROCK/NF- κ B signaling pathway is related to podocyte restoration after IT. Methods . A mouse model of diabetic nephropathy was established in vivo using streptozotocin. The mice were then subsequently reared for 4 weeks after islet transplantation to determine the effect of IT. Islet cells, CCG-1423 (RhoA Inhibitor), and fasudil (ROCK inhibitor) were then cocultured with podocytes in vitro to assess their protective effects on podocyte injury induced by high glucose (HG). Protein expression levels of RhoA, ROCK1, synaptopodin, IL-6, and MCP-1 in kidney tissues were then measured using immunohistochemistry and Western blotting techniques. Results . Islet transplantation reduced the expression levels of RhoA/ROCK1 and that of related inflammatory factors such as IL-6 and MCP-1 in the kidney podocytes of diabetic nephropathy. In the same line, islet cells reduced the expression of RhoA, ROCK1, and pp65 in immortalized podocytes under high glucose (35.0 mmol/L glucose) conditions. Conclusions . Islet transplantation can reverse podocyte injury in diabetes nephropathy by inhibiting the RhoA/ROCK1 signaling pathway. Islet cells have a strong protective effect on podocytes treated with high glucose (35.0 mmol/L glucose). Discovery of signaling pathways affecting podocyte recovery is helpful for individualized efficacy evaluation and targeted therapy of islet transplantation patients.